Analisis kepentingan-prestasi perkhidmatan Northport, Klang - Ahmad Mahir R.; Mohamed Yasser S. (Penerbit ukm, 2007)

(untitled)
This research was done to identify and assess the key determinants of service quality and the level of quality service from customer’s perception offered by Northport, Klang. The literature review identified eight important service quality factors in a port. Data for this research were collected via questionnaire directed to operational managers or marketing managers of shipping companies, the customers of Northport, Klang. The first step in this research is to examine the gap between customer’s service expectation and the actual services received. In the second step, importance-performance analysis was used to construct service attributes evaluation map to identify areas for improvement. Results revealed that all of satisfaction rating for 26 attributes were lower than the expectation rating. The gap between customer satisfaction and customer expectation exist. These results indicate that respondents did not receive the services as expected. Other results showed that respondents were not concerned about two service factors in Northport, Klang, port charge or cost and port location. They are more concerned about port management, employee, information availability of port related activities, facilities available, customer convenience and time factors